2019
DOI: 10.1371/journal.pone.0221615
|View full text |Cite
|
Sign up to set email alerts
|

A randomized pilot efficacy and safety trial of diazoxide choline controlled-release in patients with Prader-Willi syndrome

Abstract: IntroductionPrader-Willi syndrome (PWS) is a complex genetic condition characterized by hyperphagia, hypotonia, low muscle mass, excess body fat, developmental delays, intellectual disability, behavioral problems, and growth hormone deficiency. This study evaluated the safety and efficacy of orally administered Diazoxide Choline Controlled-Release Tablets (DCCR) in subjects with PWS.MethodThis was a single-center, Phase II study and included a 10-week Open-Label Treatment Period during which subjects were dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 27 publications
(34 reference statements)
1
20
1
Order By: Relevance
“…Moreover, GLWL-01, a ghrelin O-acyltransferase inhibitor, showed no significant effect on hyperphagia after 4 weeks of double-blind treatment (NCT03274856). Other therapies are being tested in PWS, such as K+-ATP channel agonists (diazoxide choline controlled released), showing a decrease in hyperphagia score in patients with the highest scores at baseline (79). Glucagon-like peptide 1 (GLP-1) receptor agonists, such as liraglutide and exenatide, have been tried out in non-randomized studies or reported in clinical cases (80,81,82).…”
Section: Toward Therapeutic Innovations In Genetic Obesitymentioning
confidence: 99%
“…Moreover, GLWL-01, a ghrelin O-acyltransferase inhibitor, showed no significant effect on hyperphagia after 4 weeks of double-blind treatment (NCT03274856). Other therapies are being tested in PWS, such as K+-ATP channel agonists (diazoxide choline controlled released), showing a decrease in hyperphagia score in patients with the highest scores at baseline (79). Glucagon-like peptide 1 (GLP-1) receptor agonists, such as liraglutide and exenatide, have been tried out in non-randomized studies or reported in clinical cases (80,81,82).…”
Section: Toward Therapeutic Innovations In Genetic Obesitymentioning
confidence: 99%
“…A Phase 2 study (PC025 pilot study) with diazoxide choline controlled-release (DCCR) tablet has been completed in children with PWS, obtaining a reduction of appetite, improvement in cardiovascular risk factors, insulin sensitivity, and a reduction in waist circumference (suggestive of a loss of visceral fat). 109 In this context, a multicenter Phase 3 clinical trial ( ClinicalTrials.gov : NCT03440814) with DCCR for the treatment of PWS was initiated in May 2018.…”
Section: Current Standard Therapiesmentioning
confidence: 99%
“…In this pilot trial, participants (aged 11‐21 years) received a 10‐week open‐label, dose‐escalation treatment with DCCR, which was followed by a 4‐week double‐blind, placebo‐controlled treatment period. In a dose‐dependent manner, treatment with DCCR was shown to significantly improve hyperphagia (n = 11, P = .006), lower the number of aggressive behaviours (n = 10, P = .01), reduce body fat mass (n = 11, P = .02), and increase lean body mass (n = 11, P = .003), with a corresponding decrease in waist circumference . Adverse events, including peripheral oedema and transient increases in glucose, were reported.…”
Section: Resultsmentioning
confidence: 98%
“…Diazoxide is a K + ‐ATP channel agonist approved for the treatment of hyperinsulinemia hypoglycaemia and acute hypertension. Diazoxide may exert therapeutic effects on PWS through the down‐regulation of insulin secretion from pancreatic β‐cells, the modulation of hypothalamic neuropeptide Y concentrations, the increase of excitability of the GABAnergic neuron, and/or the activation of K ATP channels in adipocytes . The effect of chronic diazoxide treatment on fat mass and metabolism was recently examined in mice with high‐fat diet‐induced obesity and inactivation of Magel2 , a gene also inactivated in PWS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation